Modular Teaching Technologies as Innovative Components of Modern Pedagogical Technologies - O’rinov Nodirbek Toxirjonovich; Temirova Gulbahor G’ulamovna; Yusupova Nodira Nurdinovna (International Journal on Integrated Education, 2021)
The article presents the modern content of one of the most important tasks of the formation of a multi-level system of training, retraining and advanced training of specialists. For this, the development and dissemination of innovative models, technologies and forms of organization of the educational process, as well as the introduction of modern pedagogical technologies, their innovative components and models of variable educational trajectories of learning in the systems of higher and secondary vocational education. The advantages of introducing modular teaching technologies as innovative components of modern pedagogical technologies are shown.